In vitro screening of 51 birdsfoot trefoil (Lotus corniculatus L.; Fabaceae) strains for anti-parasitic effects against Haemonchus contortus. Issue 6 (14th January 2019) - Barone, Carly D.; Zajac, Anne M.; Ferguson, Sarah M.; Brown, Rebecca N.; Reed, Jess D.; Krueger, Christian G.; Petersson, Katherine H.
Abstract: Secondary plant compounds have shown bioactivity against multi-drug resistant Haemonchus contortus in small ruminants. This study screened 51 strains of birdsfoot trefoil (BFT, Lotus corniculatus ) crude aqueous extracts (BFT-AqE) for anti-parasitic activity in vitro against egg hatching, and of those 51 strains, 13 were selected for further testing of motility of first (L1) and third stage (L3) larvae, and exsheathment of L3. Proanthocyanidin content ranged between 1.4 and 63.8 mg PAC g −1 powder across the 51 BFT strains. When tested against egg hatching, 21 of the 51 aqueous extracts had an EC50 of 1–2 mg powder mL −1, 70% of the strains were >90% efficacious at 6 mg powder mL −1 and 11 of the strains were 100% efficacious at 3 mg powder mL −1 BFT-AqE. Across the 13 strains tested against L3, efficacy ranged from 0 to 75% exsheathment inhibition, and 17 to 92% L3 motility inhibition at a concentration of 25 mg powder mL −1 BFT-AqE. There was no correlation between the PAC content of BFT powders and the anti-parasitic activity of aqueous extracts, therefore other secondary compounds may have contributed to the observed anti-parasitic effects. Further testing of BFT using bioactivity-driven fractionation and screening of BFT populations for the identified anti-parasitic compounds is needed.